Mencegah Bunuh Diri di Kalangan Orang Muda Katolik NTT Berdasarkan Perspektif Pastoral Konseling - Manu, Maximus; Mantero, Rikardus; Suhardi, Akrimianus; Lado, Sabinus Bake (Program Pascasarjana UKIM, 2024)
East Nusa Tenggara (NTT) is one of the regions frequently affected by suicide issues. The motives or reasons behind suicides in NTT are an inability to cope with the bad realities of life or a failure to face various life challenges. Therefore, this study aims to offer methods to prevent suicide more specifically through the pastoral counseling perspective, especially preventing suicide among Catholic Youth (OMK) in NTT. Because, while growing, developing, finding their identity, and trying to do useful things for their life and future, like young men and women in general, OMK is struggling with themselves and with many things outside of themselves, so OMK needs the good and correct guidance to sustain and direct them to the good and positive things, as well as preventing and keeping them away from the bad and negative things like suicide. This research uses a qualitative research method with a literature review as a means of data collection. Based on the study, it is found that the pastoral counseling perspective can help to prevent suicides among OMK in NTT because pastoral counseling has functions such as healing, sustaining, guiding, reconciling, and nurturing. These functions provide methods, stages, as well as concrete and specific steps to prevent the potential issues related to suicide among OMK in NTT so that OMK in NTT can face the bad realities of life or cope with various life challenges.